PERTUMBUHAN DAN HASIL TANAMAN TOMAT(Lycopersicum esculentum Mill.)PADA TANAH GAMBUT PEDALAMAN DENGANPEMBERIAN PUPUK ORGANIK DAN NPK (Application of NPK and Organic Fertilizers on Peat Soil to the Growth and Yield of Tomato (Lycopersicum esculentum Mill.)): Syahrudin1), Kamillah1), Renjaya, W. R. P.1) - journal journal (AgriPeat, 2017)
ABSTRACT The purposed of this experiment were to find out the interaction betweentype of organic fertilizer and dosagesof inorganicfertilizer on peat soil tothe growth and yield oftomato. The experimental units laid onFactorial Completely Randomized Design (CRD) with two factors. The first factor was three types of organic fertilizer i.e: P1: chicken manure (10 ton ha-1); P2: cow manure (10 ton ha-1); P3: compost of palm oil empty fruit bunches (10 ton ha-1). The second factor was dosage of NPK fertilizer which consisted of 4 levels: N0: without fertilizer (control); N1: 100 kg ha-1; N2: 200 kg ha- 1; N3: 300 kg ha-1. Variables measured were: plant height, number of leaves, numbers of productive branches and weight of harvested fruit.The results showed that combination of compost with NPK fertilizer doses of 300 kg ha-1 is the best in enhancing vegetative growth of plants, with plant height reaching 84,3 cm and 30 leaf sprigs. In generative phase, combination of chicken manure with the dosage of NPK 300 kg ha-1produces the heaviest tomato harvest weight, which is 379.4 g plant-1. The best dosage of NPK fertilizer in increasing the growth and yield of tomato is 300 kg ha-1. Keywords: tomato, peat soil, organic fertilizer, NPK fertilizer ABSTRAK Penelitian ini bertujuan untuk menguji interaksipemberian jenis pupuk organik dan dosis pupuk anorganik terhadap pertumbuhan dan hasil tomat pada tanah gambut pedalaman. Percobaan dirancang dalam Rancangan Acak Lengkap (RAL) Faktorial 2 faktor. Faktor pertama adalah tiga jenis pupuk organik dengan dosis 10 t ha-1, yaitu: P1= pupuk kandang ayam; P2= pupuk kandang sapi; P3= kompos tandan kosong kelapa sawit (TKKS). Faktor kedua adalah dosis pupuk NPK, yang terdiri dari 4 taraf, yaitu: N0 = tanpa pemberian pupuk (kontrol); N1 = dosis 100 kg ha-1; N2= dosis 200 kg ha-1; N3= dosis 300 kg ha-1. Variabel yang diamati adalah tinggi tanaman, jumlah daun, jumlah cabang produktif dan bobot panen buah.Hasil penelitian menunjukkan bahwakombinasi kompos TKKS dengan pupuk NPK dosis 300 kg ha-1 paling baik dalam meningkatkan pertumbuhan vegetatif tanaman, dengan tinggi tanaman mencapai 84,3 cm dan jumlah daun 30 tangkai.Padafase generatif, kombinasi pupuk kandang ayam dengan dosis pupuk NPK 300 kg ha-1 menghasilkan bobot panen tomat terberat, yaitu 379,4 g tan-1.Dosis pupuk NPK yang terbaik dalam meningkatkan pertumbuhan dan hasil tanaman tomat adalah 300 kg ha-1. Kata kunci : Tomat, tanah gambut, pupuk organik, pupuk NPK.